DRUG SALES WEB-BASED INFORMATION SYSTEM AT DILA FARMA PHARMACY USING WATERFALL METHOD - Safera, Agna; Ricky Martin, Mohamad; Hidayat, Taufik; Surya Permana, Indra (Universitas Perwira Purbalingga, 2022)
The volume of data and information that must be handled makes manual processing impossible. A tool with a high degree of computation speed and data delivery is necessary for processing a massive volume of data. These instruments consist of hardware and software, Dila Farma Pharmacy is a pharmacy that still uses manual techniques to calculate the sale of medications, such as documenting pharmaceuticals and their pricing in a ledger. This manual technique requires considerable time and effort and is prone to error. This project aims to develop a medicine distribution system that can facilitate data processing computations. This study's objective is to build and develop a web-based application for processing drug data and comprehensive information on the sorts of pharmaceuticals used at Dila Farma Pharmacy.